The role of ion channels in light-dependent stomatal opening. - Dietrich, Petra; et al. (Journal of Experimental Botany, 2001)
Stomatal opening represents a major determinant of plant productivity and stress management. Because plants lose water essentially through open stomata, volume control of the pore-forming guard cells represents a key step in the regulation of plant water status. These sensory cells are able to integrate various signals such as light, auxin, abscisic acid, and CO(2). Following signal perception, changes in membrane potential and activity of ion transporters finally lead to the accumulation of potassium salts and turgor pressure formation. This review analyses recent progress in molecular aspects of ion channel regulation and suggests how these developments impact on our understanding of light- and auxin-dependent stomatal action.